Jet fuel exposure and auditory outcomes in Australian air force personnel - Adrian Fuente; Louise Hickson; Thais C. Morata; Warwick Williams; Asaduzzaman Khan; Eduardo Fuentes-Lopez (BMC, 2019)
Abstract Background Animal data suggest that jet fuels such as JP-8 are associated with hearing deficits when combined with noise and that the effect is more pronounced than with noise exposure alone. Some studies suggest peripheral dysfunction while others suggest central auditory dysfunction. Human data are limited in this regard. The aim of this study was to investigate the possible chronic adverse effects of JP-8 combined with noise exposure on the peripheral and central auditory systems in humans. Methods Fifty-seven participants who were current personnel from the Royal Australian Air Force were selected. Based on their levels of exposure to jet fuels, participants were divided into three exposure groups (low, moderate, high). Groups were also categorised based on their noise exposure levels (low, moderate, high). All participants were evaluated by tympanometry, pure-tone audiometry (1-12 kHz), distortion product otoacoustic emissions (DPOAEs), auditory brainstem response (ABR), words-in-noise, compressed speech, dichotic digit test, pitch pattern sequence test, duration pattern sequence test and adaptive test of temporal resolution. All auditory tests were carried out after the participants were away from the Air Force base for a minimum of two weeks, thus two weeks without jet fuel and noise exposure. Results Jet fuel exposure was significantly associated with hearing thresholds at 4 and 8 kHz; average hearing thresholds across frequencies in the better ear; DPOAEs at 2.8, 4 and 6 kHz; ABR wave V latency in the right ear; compressed speech and words-in-noise. Further analyses revealed that participants with low exposure level to jet fuels showed significantly better results for the aforementioned procedures than participants with moderate and high exposure levels. All results were controlled for the covariates of age and noise exposure levels. Conclusions The results suggest that jet fuel exposure, when combined with noise exposure, has an adverse effect on audibility in humans. Taking all the test results into consideration, jet fuel exposure combined with noise exposure specifically seems to affect the peripheral hearing system in humans.